Polimorfisme g.-371T>A Promotor Gen Miostatin pada Sapi Pedaging Indonesia - Sutikno Sutikno; Rudy Priyanto; Cece Sumantri; Jakaria Jakaria (Jurnal Ilmu Pertanian Indonesia, 2020)
Myostatin (MSTN) gene acts as a negative regulator of muscle growth. The aim of the present study was to identify polymorphism of g.-371T>A in promoter region of MSTN gene in Indonesian beef cattle. Blood samples were collected from 191 cattle, including Bali (BL) (42), Madura (MD) (20), Pesisir (PI) (17), Katingan (KT) (16), Ongole grade (PO) (22), Pasundan (PD) (14), Sumba ongole (SO) (10), Brahman (BH) (17), Simmental (SM) (15), and Limousin (LM) (18). Polymorphism of MSTN gene was analyzed using PCR-RFLP (DraI) and direct sequencing methods. Results of genotyping g-371T>A were polymorphic (TT, TA, and AA genotypes) in Simmental, SO, and Katingan. The frequencies of alleles T and A were 0.83; 0.90; 0.97 and 0.17; 0.10; 0.03 respectively. The values of Ho and He were 0.06–0.20 and 0.06–0.28, respectively. The results of this study are in Hardy-Weinberg equilibrium (P> 0.05). Whereas in PD, MD, PI, PO, BH, LM, and BL were monomorphic (TT genotype). The result of sequencing the promoter region of MSTN gene found that mutations transversion was occurred in T to A at g.-371. It was concluded that g.-371T>A of MSTN gene was polymorphic which was potential to be used as genetic markers of muscle growth in SM, SO, and KT cattle. Keywords: SNP g.-371T>A of MSTN gene, Sumba ongole cattle, Katingan cattle, Simmental cattle